Description of a new leafhopper species of the genus Sophonia Walker (Hemiptera: Cicadellidae: Evacanthinae) from China - Gou, Guangli; Xing, Jichun (Zootaxa, 2024)
A new leafhopper species Sophonia furcata sp. nov., is described and illustrated from Sichuan Province, China. A key is given to distinguish all Chinese species of the genus. The type specimens of the new species are deposited in the Institute of Entomology, Guizhou University, Guiyang, China (GUGC).